SITUASI DIGLOSIA SUKU BONAI DI PROVINSI RIAU - Imelda Yance (Balai Bahasa Provinsi Riau, 2017)
Bonai ethnic/people (indigenous and minority people in Riau Province) is a bi/multilingual society. They have the potential to be a diglossic society because mastering and using more than one language in communication. To find out the potential, this study focused on the diglossia of the Bonai ethnic.The aims are to define and describe the status of the Bonai people diglossia in terms of function, prestige, cultural heritage, acquisition, standardization, stability, lexicon, andphonological systems. This study is quantitative and qualitative. Data were collected through surveys using questionnaires and literature studies. The sample numbered is 78 people, drawn by purposive random technique. Quantitative data is processed by Excel and SPSS program and qualitative data with discourse analysis. From the data analysis, the Bonai people can be categorized as both diglossia and bilingualism. The conclusions are based on the aspects of function, prestige, acquisition, standardization, lexicon, and phonological systems. Indonesian is H code (high) while the language of Bonai people is L code (low). Nevertheless, the situation of diglossia in the Bonai people has not been steady in terms of stability since it has not taken place in hundreds of years. In addition, there is also a leaked of diglossia, the infiltration of L code into the domain of H code or vice versa.